PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN RUMAH DI GOLDEN CITY RESIDENCE KOTA BATAM - Ci, Angela Mari; Raymond, Raymond (SCIENTIA JOURNAL, 2021)
This study aims to know the influence and analyze the quality product and promotion on house purchase decisions at Golden City Residence Batam City.This research has three variables which consisting of two variables independent which quality product as variable X1,promotion as X2 and it consist of one variable dependent which purchases decision as variable Y.This research data analysis method using quantitative data analysis, and using descriptive research, primary data collection tools using a questionnaire which was distributed to customer PT Alam Jaya Sentosa of this research is 118 people. . In this research, researchers used probability sampling techniques which included saturated samples, The data is processed using SPSS version 24. The results of the multiple linear regression analysis equation are Y = 13,147 + 0,227.X1 + 0,422.X2. Based on the results of the determination test, 37.7% are explained by variables product quality and promotion, the rest was explained by other variables not discussed in this study. The result showed that partially the quality product and promotion positive effect and significance of a purchase decision.